The Foundation, Role, Direction of Education in Indonesia, Along with Responsibilities, Authorities and What Educators Must Do - Maspuroh; Ramdan Nafilah; M. Azhar Busaeri Putra; Fredy Ismail (Responsive: Jurnal Manajemen Pendidikan Islam, 2025)
Education in Indonesia plays a crucial role in shaping character and developing human resource potential. Based on Pancasila and the 1945 Constitution, Law Number 20 of 2003 concerning the National Education System establishes the basic principles of education that are just, democratic, inclusive, and non-discriminatory. This legal framework also emphasizes respect for human rights, religious values, and national cultural diversity. Through this approach, education in Indonesia not only aims to educate the nation, but also strengthen the identity and noble values of society in facing global challenges. The national education system is designed to create a holistic learning environment, preparing students to become a competent generation, with noble character, and contributing positively to national development.